Study of pathologies on flexible floors in the city of Teófilo Otoni, Minas Gerais State, Brazil (Research, Society and Development, 2021)
It is a function of the highways to provide comfort, safety, and good rolling conditions to users. Therefore, the roads must be correctly designed showing adequate quality and durability for use. However, what is observed in Brazil is that most of the existing roads are not in good condition due to the number of pathologies found in them, bringing discomfort and insecurity to users. Bearing in mind that the flexible floor is the most used in the country, it is necessary to study the defects found during its useful life, which may be of structural or functional origin, to offer adequate maintenance and possibly better-rolling conditions to those who travel through it. Thus, the present study tackles pathological problems observed on a flexible pavement in the Municipality of Teófilo Otoni, Brazil, its possible causes, and some proposals for measures to be taken in the construction and maintenance processes to reduce the appearance of these pathologies. In addition, the identification and classification of pathologies and nonconformities found in the studied places were carried out. Thus, there was a need for maintenance so that its functionality is not affected, requiring the use of recovery techniques through resurfacing or a sealing layer, improving drainage and milling, which provides longer life and avoids inconvenience to users.